2005
DOI: 10.1520/jfs2005178
|View full text |Cite
|
Sign up to set email alerts
|

Seven Hundred Seventy Eight Bite Marks: Analysis by Anatomic Location, Victim and Biter Demographics, Type of Crime, and Legal Disposition

Abstract: A study of the etiology, anatomic location, victim demographics and legal disposition of bite mark cases was made with the purpose of updating and augmenting previous research in the field. The information may be of interest to a myriad of professional disciplines including Forensic Odontologists, Medical Examiners, Detectives, Profilers, Emergency Room Personnel, Coroners, Psychologists, and Family Service Counselors, as bite marks provide both physical and biological data. While bite marks were found on all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 7 publications
2
25
2
2
Order By: Relevance
“…These proportions are similar to studies conducted in Ilam, Tehran and Kerman provinces of the Islamic Republic of Iran, where it was reported that 68.3%, 79.2% and 73.5% of animal bites respectively were to men (11)(12)(13)(14). On the other hand, the results of a study performed in the United States of America (USA) indicated that women were more frequently injured by animals as compared to men (15). Another study, performed in Puerto Rico, showed that the rate of animal bites was similar in both women and men (16).…”
Section: Discussionmentioning
confidence: 99%
“…These proportions are similar to studies conducted in Ilam, Tehran and Kerman provinces of the Islamic Republic of Iran, where it was reported that 68.3%, 79.2% and 73.5% of animal bites respectively were to men (11)(12)(13)(14). On the other hand, the results of a study performed in the United States of America (USA) indicated that women were more frequently injured by animals as compared to men (15). Another study, performed in Puerto Rico, showed that the rate of animal bites was similar in both women and men (16).…”
Section: Discussionmentioning
confidence: 99%
“…It also excludes the closing action of jaws during intended biting if a recognizable pattern is not produced. 20,[23][24][25][26] These other tooth-to-skin interactions are still important even if not distinguished by the term "Bite mark" because they can be responsible for infection, tissue destruction, or transmissible diseases, and they can transfer DNA in saliva. 11 However, by convention, the term "Bite mark" signifies to the forensic odontologist an injury that, by its pattern, helps establish its origin from teeth.…”
Section: 1112mentioning
confidence: 99%
“…Males are commonly bitten on the arms, shoulders and back. 4 Hands and arms are commonly bitten when a victim is attempting defence actions.…”
Section: Anatomical Distribution Of Bite Marksmentioning
confidence: 99%